A new framework and a hybrid method for one-dimensional population balance modeling of batch thermocycling crystallization. (January 2022) - Kang, Yung-Shun; Ward, Jeffrey D.; Nagy, Zoltán K.
Highlights: A novel hybrid method is proposed to solve population balance models. The approach combines high-resolution finite volume and method of moments. Specially tailored for crystallizations with thermocycles with switching mechanisms. Efficient implementation as C/Mex file increases computational performance. Demonstrated for the thermocycling crystallization of paracetamol and l -ascorbic acid. Abstract: The hybrid method (HM) presented in this article assembles the high-resolution finite volume method (HRFVM) and the standard method of moments (SMOM) with an accurate inversion technique for determining the crystal size distribution (CSD), providing a computationally efficient solution with reliable accuracy for one-dimensional population balance modeling in batch thermocycling crystallizations. Two chemical systems, paracetamol and l -ascorbic acid, are chosen to study the accuracy and computational efficiency of the approach in the unseeded and seeded cases, respectively. Comparisons between the HRFVM and the HM are made for different temperature profiles in both cases. In addition, the compiled C/Mex files (MXFs) are implemented to further minimize the run time of the HM, and the benefits of the compiled files are discussed compared to the MATLAB files (MAFs).